2018
DOI: 10.3390/brainsci8120204
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Closed-Loop Transcranial Alternating Current Stimulation on Subjective Sleep Quality

Abstract: Background: Poor sleep quality is a common complaint, affecting over one third of people in the United States. While sleep quality is thought to be related to slow-wave sleep (SWS), there has been little investigation to address whether modulating slow-wave oscillations (SWOs) that characterize SWS could impact sleep quality. Here we examined whether closed-loop transcranial alternating current stimulation (CL-tACS) applied during sleep impacts sleep quality and efficiency. Methods: CL-tACS was used in 21 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…One that used high-definition direct current tES targeting the left prefrontal cortex in elders observed an increase in subjective sleep duration and sleep efficiency in the active group vs. a waiting list group (73). Similarly, a crossover study that tested slow alternating tES during sleep found higher sleep quality and efficiency after active vs. sham stimulation (72). A study that specifically investigated frontal stimulation in athletes observed a global improvement in subjective sleep after two consecutive active stimulation sessions in comparison to a group that received sham stimulations (71).…”
Section: Results From Studies In Healthy Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…One that used high-definition direct current tES targeting the left prefrontal cortex in elders observed an increase in subjective sleep duration and sleep efficiency in the active group vs. a waiting list group (73). Similarly, a crossover study that tested slow alternating tES during sleep found higher sleep quality and efficiency after active vs. sham stimulation (72). A study that specifically investigated frontal stimulation in athletes observed a global improvement in subjective sleep after two consecutive active stimulation sessions in comparison to a group that received sham stimulations (71).…”
Section: Results From Studies In Healthy Populationmentioning
confidence: 99%
“…Fifteen studies investigated the impact of tES on subjective aspects of sleep in healthy ( 45 , 52 , 71 73 ) and clinical samples ( 41 44 , 46 , 48 , 66 , 74 81 ). Most used parallel arms ( 45 , 52 , 66 , 72 ) or crossover-controlled designs ( 41 43 , 46 , 71 , 73 , 74 , 78 , 80 , 81 ). The others were uncontrolled series or case reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During sleep for instance, tACS was triggered during fast spindles to enhance motor memory consolidation [46]. The effects of closed-loop tACS in memory consolidation have been confirmed in other studies [47,48] and this setup has shown therapeutic benefits in sleep quality [49], and tremor suppression [50]. The field of closed-loop application of non-invasive brain stimulation is still subject to important challenges such as development of accurate and optimized triggering algorithms, translation to clinical use and correct identification of inputs to feed the system with.…”
Section: Discussionmentioning
confidence: 69%
“…For example, if physical encumbrance and exertion is particularly influential for sustained performance across domains of interest, it may warrant increased investment in strength and endurance training, lower-extremity exoskeletons, or other approaches for reducing physical and physiological burden of continuous operations (Gregorczyk et al, 2010;Ozaki et al, 2013;Scribbans et al, 2016;Seo et al, 2018;Wei et al, 2020;Shepertycky et al, 2021). The same might be said for sleep or stress, identifying methods for increasing the quality or duration of naps and overnight sleep (Irwin et al, 2008;Ketz et al, 2018;Robinson et al, 2018), and/or reducing the intensity of stress responses (Stanley et al, 2011;Jaremko and Meichenbaum, 2013). As additional predictors are incorporated into the model, it will afford a more robust ranking and prioritization of cognitive and/or physical states that are most negatively impactful for performance and motivate research and development toward mitigating such impacts.…”
Section: Software Tool Implementationmentioning
confidence: 99%